Extensive spinal epidural abscess due to Streptococcus intermedius: a case report treated conservatively and literature review - Liu, Dianqi; Lu, Weijie; Huang, Wenbin; Zhai, Wenrun; Ling, Qinjie (Frontiers in Neurology, 2023)
Streptococcus intermedius: a case report treated conservatively and literature review Purpose. To describe the clinical significance of prompt, adequate, and targeted intravenous antibiotic (IV antibiotic) therapy in the successful management of spinal epidural abscess (SEA) associated with Streptococcus intermedius (S. intermedius) infection. Case description. SEA is a rare, but catastrophic infection that may result in a high risk of permanent neurological disability. A 52-year-old Chinese female patient was presented to the emergency department due to 2 years of low back pain and 3 days of decreased muscle strength in the extremities. The blood culture confirmed the presence of S. intermedius infection, and gadolinium-enhanced magnetic resonance imaging (MRI) demonstrated widespread epidural abscesses in the cervical, thoracic, and lumbar spine canal. Empirical IV antibiotic therapy with vancomycin was promptly initiated, with meropenem and moxifloxacin added subsequently based on blood culture results. After 5 days of IV antibiotic treatment, the patient's blood culture became negative. 6 weeks later, a follow-up MRI showed a decrease in the size of the abscess. The patient's muscle strength was mostly restored after 2 months of IV antibiotic treatment.should be considered when initial MRI findings are not diagnostic of SEA.For extensive SEA caused by Streptococcus intermedius infection, surgery may be non-essential, and the judicious antibiotic selection and adequate treatment duration are pivotal for successful conservative management. Furthermore, for patients who are not amenable to surgery, a comprehensive evaluation of their condition and meticulous implementation of a precise pharmacological regimen holds noteworthy clinical significance.